Fibrin clot structure is affected by levels of particulate air pollution exposure in patients with venous thrombosis. (July 2016) - Pan, Xiaoxi; Gong, Yun Yun; Martinelli, Ida; Angelici, Laura; Favero, Chiara; Bertazzi, Pier Alberto; Mannucci, Pier M.; Ariëns, Robert A.S.; Routledge, Michael N.
Abstract: Background: Particulate air pollution is a risk factor for cardiovascular diseases and thrombosis. Long-term exposure to particulate matter with a diameter < 10 μm (PM10 ) has been associated with an increased risk of venous thrombosis. Objectives: The aim of this study was to investigate whether or not particulate air pollution alters fibrin clot structure and thus modulates thrombosis risk. Methods: We investigated fibrin polymerization by turbidity (maximum absorbance mOD), clot structure by confocal microscopy (fibre number per μm) and fibrin pore size by permeability (Ks × 10 − 10  cm 2 ) in 103 patients with deep vein thrombosis and 121 healthy controls, for whom levels of air pollution exposure had been recorded. Exposure groups were defined by mean PM10 concentrations over the 730 days before the event. Results: We found a higher average number of fibres per clot area in patients than controls, but no difference in Ks or fibre thickness. When the two groups were divided into high or low exposure to PM10, a significantly denser fibrin clot network structure with thicker fibres (higher maximum absorbance, p < 0.05), decreased permeability (lower Ks value, p < 0.05) and higher average fibre numbers per clot area (p < 0.05) was observed in patients in the high exposure group compared to those with low exposure. There were no significant differences in fibrin clot structure between the two exposure levels in healthy subjects. Conclusions: PM10 levels are associated with altered fibrin clot structure in patients with deep vein thrombosis but not in controls, suggesting that air pollution may trigger differences in fibrin clot structure only in patients predisposed to thrombotic disease. Highlights: PM10 levels are associated with denser fibrin clot structure in patients with DVT. In the control group, high PM10 level did not contribute to denser fibrin clot structure formation. Air pollution may trigger differences in clot structure in patients predisposed to thrombosis.